Fiduciary Guarantee Agreement in Relation to Constitutional Court Decision Number: 18/PUU-XVII/2019 - Nasution , Ahmad Julyadi; Kamello , Tan; Purba , Hasim; ., Saidin (Journal of Ecohumanism, 2025)
An agreement is an event where a person promises another party to carry out something.. Bank and non-bank financing institutions distribute funds to the public in the form of credit with collateral, one of which is a fiduciary guarantee. When implementing the agreement, defaults sometimes occur. With the issuance of the Constitutional Court's decision Number 18/PUU-XVII/2019, disputes were resolved through a court decision. In contrast, previous disputes without a court decision were resolved by withdrawing the collateral Object based on the deed of agreement and fiduciary guarantee certificate. Based on the description above, the problem of this research is the position of fiduciary guarantee deeds with the issuance of Constitutional Court decision Number 18/PUU-XVII/2019 and the practice of executing fiduciary guarantees carried out by financing institutions. This research method uses normative juridical methods. Fiduciary guarantee deeds and fiduciary guarantee certificates have the power as proof of creditors holding fiduciary guarantees. Fiduciary recipients can immediately execute the action of collateral. With the Constitutional Court's decision, it certainly slows down execution in practice. Fiduciary guarantee deeds and fiduciary guarantee certificates have the same executorial power as court decisions. In the Constitutional Court's decision, the execution of fiduciary guarantees is carried out based on the court's decision if the fiduciary guarantee deed does not mention default. The fiduciary guarantee deed and guarantee certificate must still be a means of executing the guarantee without going through a court decision.